PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Rofikhatul Ula, Wahyu Rikha; Nugraha, Yoga Awalludin (Institut Daarul Qur'an Jakarta, Indonesia, 2023)
This study aims to analyze the effect of the Problem Based Learning (PBL) learning model on the understanding of mathematical concepts. The research method used in this research is a quantitative method in the form of one group pre-post design. The sample of this study was class VI SD 5 Gondangmanis, which consisted of 18 students. The data collection technique is a test and non-test, the test technique uses questions of understanding mathematical concepts while the non-test technique uses observation and documentation. Data analysis techniques using the normality test and t test. The results of the data analysis concluded that there was an influence of the PBL learning model on the ability to understand mathematical concepts in class VI SD 5 Gondangmanis. This is evident from the results of the paired sample t-test, the results obtained were 0.00 <0.05, meaning that H0 was rejected, meaning that the PBL model had an effect on the understanding of mathematical concepts in class VI students at SD 5 Gondangmanis.